2004
DOI: 10.1023/a:1025867130437
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinases (MMPs) in colorectal cancer

Abstract: Considerable evidence has implicated matrix metalloproteinases (MMPs), a group of zinc-dependent endopeptidases, in the degradation of extracellular matrix (ECM) during the metastatic process. Most MMPs are secreted as inactive zymogens and are activated extracellularly. Over expression of MMP-1, -2, -3. -7, -9, -13, and MT1-MMP has been demonstrated in human colorectal cancers. The degree of over expression of some MMPs has been noted to correlate with stage of disease and/or prognosis. An unresolved debate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
329
1
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(350 citation statements)
references
References 102 publications
11
329
1
9
Order By: Relevance
“…Similar to AKT, MMP3 can also cause epithelial -mesenchymal transition in cancer (Radisky et al, 2005). Matrix metalloproteinase 9 plays a central role in connective tissue degradation, tumourinduced angiogenesis, cell proliferation/apoptosis and cell migration in various tumour types including cervical cancer (van Kempen and Coussens, 2002;Van Trappen et al, 2002;Zucker and Vacirca, 2004;Vazquez-Ortiz et al, 2005b). Recently, one study has shown that MMP9 forms a complex with the hyaluronan receptor CD44 on the surface of breast cancer cells and activates downstream TGF-b, facilitating tumour cell survival, invasion and metastasis (Yu and Stamenkovic, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to AKT, MMP3 can also cause epithelial -mesenchymal transition in cancer (Radisky et al, 2005). Matrix metalloproteinase 9 plays a central role in connective tissue degradation, tumourinduced angiogenesis, cell proliferation/apoptosis and cell migration in various tumour types including cervical cancer (van Kempen and Coussens, 2002;Van Trappen et al, 2002;Zucker and Vacirca, 2004;Vazquez-Ortiz et al, 2005b). Recently, one study has shown that MMP9 forms a complex with the hyaluronan receptor CD44 on the surface of breast cancer cells and activates downstream TGF-b, facilitating tumour cell survival, invasion and metastasis (Yu and Stamenkovic, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Metalloproteinases are inhibited by tissue inhibitors (TIMPs) which are secreted proteins. These bioactive substances are specific inhibitors of MMPs that bind to enzymatically active MMPs at a 1:1 molar stoichiometry thus inhibiting proteolysis.…”
mentioning
confidence: 99%
“…The tumor cell integrin binded to ECM ligands activating a form of intracellular signaling promoting cell invasion and metastasis; this type of adhesion molecules dependent intracellular signal transduction was generally called "outside-in signaling" (Giancotti et al, 1999). On the other hand, mold metalloproteinases (MMPs) were a family of zinc-dependent neutral endopeptidases that had a crucial role in the degradation of extracellular matrix, which were crucial for malignant tumor growth, invasion, and metastasis (Zucker et al, 2004). Ozgur Kemik et al investigated MMP-1 level in gastric cancer patients and compared them with a control group.…”
Section: Discussionmentioning
confidence: 99%